2007
DOI: 10.1128/mcb.00248-07
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms Involving Diverse Histone Deacetylases Repress Expression of the Two Gonadotropin β-Subunit Genes in Immature Gonadotropes, and Their Actions Are Overcome by Gonadotropin-Releasing Hormone

Abstract: The gonadotropins luteinizing hormone (LH) and follicle-stimulating hormone (FSH) are produced in the embryonic pituitary in response to delivery of the hypothalamic gonadotropin releasing hormone (GnRH). GnRH has a pivotal role in reestablishing gonadotropin levels at puberty in primates, and for many species with extended reproductive cycles, these are reinitiated in response to central nervous system-induced GnRH release. Thus, a clear role is evident for GnRH in overcoming repression of these genes. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 71 publications
0
81
2
Order By: Relevance
“…The reason why FSH␤ is insensitive to HDAC induction is thought to be due to the isoform specificity in the induction of HDAC by TCDD. It has been reported that while HDAC1, 5, and 7 are preferentially associated with the repression of LH␤ gene, HDAC2 and 3 mainly contribute to the suppression of FSH␤ transcription (33). In the present study, although HDAC1, 5, and 7 were induced in the fetal and neonatal pituitary by maternal exposure to TCDD, HDAC2 was not sensitive to TCDD treatment.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The reason why FSH␤ is insensitive to HDAC induction is thought to be due to the isoform specificity in the induction of HDAC by TCDD. It has been reported that while HDAC1, 5, and 7 are preferentially associated with the repression of LH␤ gene, HDAC2 and 3 mainly contribute to the suppression of FSH␤ transcription (33). In the present study, although HDAC1, 5, and 7 were induced in the fetal and neonatal pituitary by maternal exposure to TCDD, HDAC2 was not sensitive to TCDD treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…It has been suggested that HDAC plays an important role as a transcriptional repressor for gonadotropin ␤-subunits (19,32,33). In agreement with this, TCDD markedly deacetylated histones H3 and H4 twined around the promoter of the fetal LH␤ gene, but not the promoters of other pituitary hormone genes (FSH␤, ␣GSU, TSH␤, and GH).…”
Section: Discussionmentioning
confidence: 60%
“…It also induces an increase in intracellular calcium levels by stimulating calcium release from intracellular stores as well as the influx of extracellular calcium through voltage-sensitive channels (7, 42). One of the effects of this increase in calcium levels is the activation of calmodulin and calmodulin-dependent kinases (CaMKs), which mediate various aspects of GnRH-induced signaling, including inhibition of histone deacetylases and regulation of extracellular signal-regulated kinase (ERK) activity (6,10,23,24,34,44,61). Calmodulin also activates the serine/threonine protein phosphatase calcineurin to regulate the expression of various genes (26).…”
mentioning
confidence: 99%
“…Lim et al previously reported that the gonadotropin β-subunit gene was repressed by histone deacetylase in immature gonadotrophs such as αT3-1 cells and LβT2 cells. They further found that GnRH activation of calcium/calmodulin-dependent protein kinase I plays a crucial role in the derepression of the FSHβ gene by phosphorylation of histone deacetylase [27]. These finding suggest that GnRH could also modulate the activity of histone modifying enzymes in gonadotrophs.…”
Section: Figmentioning
confidence: 91%